IDENTIFIKASI KERUSAKAN MESIN TWIN SCREW PENGOLAHAN KARET BASAH DENGAN METODE FAILURE MODE AND EFFECT ANALYSIS DI PT. WILSON LAUTAN KARET - Imron Musthofa Imron; Titik Wijayati; Ilyas Sofana; Elandi (P3M Politeknik Negeri Tanah Laut, 2023)
Wilson Lautan Karet is a rubber processing company in Banjarmasin that processes wet rubber into crumb rubber or Crum Rubber by producing semi-finished products namely SIR 20 and SIR 10. Products SIR 20 PT. Wilson Lautan Karet often experiences damage such as contamination and defects in the SIR product, which can be seen in the final part, sorting. Product damage is also caused by machines that are starting to get damaged and dirty so they need maintenance or maintenance (maintenance) on the machines used for production. In this study, the identification of damage to the wet rubber processing Twin Screw machine occurred at PT. Wilson Lautan Karet Banjarmasin and this identification uses the methodFailure Mode And Effect Analysis. The steps are to collect data from observations, interviews, documentation, and data in the form of reports on machine repairs and product results, identify problems with the methodFailure Mode and Effect Analysis (FMEA), and analysis using cause and effect diagrams (fishbone diagram). Based on the RPN critical value obtained, 3 critical risks are found in the Twin Screw engine components, namely the gear joint with a total RPN of 144, axle screw of 189, and bearing of 147. The value of the three risks is above the RPN critical value, namely of 131. It can be concluded that the following components are at risk with the highest RPN values, namely the gear joint, screw axle, and bearing. These three components pass the RPN critical value limit of 131.